A pilot precision medicine trial for children with diffuse intrinsic pontine glioma—PNOC003: A report from the Pacific Pediatric Neuro‐Oncology Consortium. Issue 7 (3rd April 2019) - Mueller, Sabine; Jain, Payal; Liang, Winnie S.; Kilburn, Lindsay; Kline, Cassie; Gupta, Nalin; Panditharatna, Eshini; Magge, Suresh N.; Zhang, Bo; Zhu, Yuankun; Crawford, John R.; Banerjee, Anu; et al.
Abstract : This clinical trial evaluated whether whole exome sequencing (WES) and RNA sequencing (RNAseq) of paired normal and tumor tissues could be incorporated into a personalized treatment plan for newly diagnosed patients (<25 years of age) with diffuse intrinsic pontine glioma (DIPG). Additionally, whole genome sequencing (WGS) was compared to WES to determine if WGS would further inform treatment decisions, and whether circulating tumor DNA (ctDNA) could detect the H3K27M mutation to allow assessment of therapy response. Patients were selected across three Pacific Pediatric Neuro‐Oncology Consortium member institutions between September 2014 and January 2016. WES and RNAseq were performed at diagnosis and recurrence when possible in a CLIA‐certified laboratory. Patient‐derived cell line development was attempted for each subject. Collection of blood for ctDNA was done prior to treatment and with each MRI. A specialized tumor board generated a treatment recommendation including up to four FDA‐approved agents based upon the genomic alterations detected. A treatment plan was successfully issued within 21 business days from tissue collection for all 15 subjects, with 14 of the 15 subjects fulfilling the feasibility criteria. WGS results did not significantly deviate from WES‐based therapy recommendations; however, WGS data provided further insight into tumor evolution and fidelity of patient‐derived cell models. Detection of the H3F3A or HIST1H3B K27M (H3K27M) mutation using ctDNA was successful in 92% of H3K27M mutant cases. A personalized treatment recommendation for DIPG can be rendered within a multicenter setting using comprehensive next‐generation sequencing technology in a clinically relevant timeframe. Abstract : What's new? While children diagnosed with diffuse intrinsic pontine glioma (DIPG) continue to suffer dismal survival outcomes, progress in next‐generation sequencing technologies have advanced the possibility of personalized therapeutic interventions. This prospective study demonstrates the feasibility of performing biopsies on patients with DIPG at diagnosis, applying approaches in next‐generation sequencing to determine an individualized therapy plan in a clinically relevant timeframe. Analyses of cell lines derived from patient samples revealed key genomic alterations typical of DIPG, including mutations in ACVR1, H3F3A / HIST1H3B, PIK3R1, PPM1D, and TP53 . The study further highlights the utility of circulating tumor DNA for detecting driver mutations in DIPG.